2016
DOI: 10.1016/j.bbr.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor antagonism disrupts acquisition and retention of the context preexposure facilitation effect in adolescent rats

Abstract: The context preexposure facilitation effect (CPFE) is a contextual fear conditioning paradigm in which learning about the context, acquiring the context-shock association, and retrieving/expressing contextual fear are temporally dissociated. The current study investigated the involvement of NMDA receptors in contextual fear acquisition, retention, and expression across all phases of the CPFE in adolescent rats. In Experiment 1 systemic injections of 0.1 mg/kg MK-801, a non-competitive NMDA receptor antagonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…al., ). Both measures of freezing are also disrupted by systemic administration of MK‐801 in adolescent (PD31) rats, although retention‐test freezing is more sensitive than post‐shock freezing to the dose of MK‐801 (Heroux et al, ). Other studies have shown that post‐shock freezing in the sCFC paradigm is present in PD18 rats and retention freezing begins to develop around PD23 (Rudy, ; Rudy & Morledge, ; Stanton, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…al., ). Both measures of freezing are also disrupted by systemic administration of MK‐801 in adolescent (PD31) rats, although retention‐test freezing is more sensitive than post‐shock freezing to the dose of MK‐801 (Heroux et al, ). Other studies have shown that post‐shock freezing in the sCFC paradigm is present in PD18 rats and retention freezing begins to develop around PD23 (Rudy, ; Rudy & Morledge, ; Stanton, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that NMDARs are involved in learning tasks during the pre‐weanling period of development (Highfield, Nixon, & Amsel, ; Langton, Kim, Nicholas, & Richardson, ; Lincoln, Coopersmith, Harris, Cotman, & Leon, ). The role of NMDARs in learning and memory has been previously examined by our lab in developmental studies of the CPFE (Heroux et al, ; Schiffino et al, ) and various hippocampal‐dependent object recognition tasks (Jablonski, Schreiber, Westbrook, Brennan, & Stanton, ; Ramsaran, Sanders, & Stanton, ); as well as T‐maze working memory and reversal tasks (Chadman, Watson, & Stanton, ; Watson, Herbert, & Stanton, ; Watson & Stanton, ). In the CPFE, systemic NMDAR antagonism during context preexposure or training phases disrupts retention test freezing in PD24 and PD31 rats (Burman, Murawski, Schiffino, Rosen, & Stanton, ; Heroux et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fear conditioning occurred in four clear Plexiglas chambers designated as Context A as described previously (Heroux, Robinson-Drummer, Rosen, & Stanton, 2016; Murawski & Stanton, 2010; Robinson-Drummer et al, 2016). The chambers measured 16.5 × 12.1 × 21.6 cm and were arranged in a 2 × 2 formation on a Plexiglas stand within a fume hood which provided ambient light and background noise.…”
Section: General Methodsmentioning
confidence: 99%